PENGARUH MEDIA PEMBELAJARAN DAN KECERDASAN GANDA TERHADAP HASIL BELAJAR TEKNOLOGI INFORMASI DAN KOMPUTER (TIK) MAHASISWA PGSD UNIVERSITAS NEGERI MEDAN - Harun Sitompul; Reni Astuti (Universitas Negeri Medan, 2012)
Abstract: The Effect Of Instructional Media And Multiple Intelligences On Student’s Learning Achievement On Information And Comunication Technology (ICT) Of Primary Teacher Education, State University Of Medan. The objectives of this quasi – experimental research were to discover: 1) whether the students learning achievement of Primary Teacher Education (PTE) in ICT taught by using CD interactive multimedia interactive instructional media was higher than learning achievement of PTE taught by using module instructional media, 2) whether the students learning achievement of PTE in ICT with spasial visual multiple intelligences was higher than student’s with verbal linguistic multiple intelligences, and 3) the interaction between instructional media and multiple intelligences in affecting the student’s learning achievement in ICT. The population of the study was 180 students of PTE who took the ICT from 6 classes namely 2 regular classes, 3 extension classes from the city government Academic year 2010/2011.Based on cluster random sampling technique 4 clasess taken from 2 reguler classes and 2 extention classes. The A regular class and A extension class using CD interactive multimedia instructional media and module was used in B regular class and B extention class. The research findings showed that : (1) the students’ learning achievement in ICT taught by using CD interactive multimedia instructional media was higher than the students’ taught by using module instructional media with Fcount = 11.65 > Ftables = 4.00 at the level of significance α = 0.05; (2) the students’ learning achievement in ICT with multiple intelligences spatial visual was higher than students’learning achievement with multiple intelligences verbal linguistic with Fcount = 11.65 > Ftables = 4.00 at the level of significance α = 0.05, and (3) there was an interaction between instructional media and multiple intelligences on students’ learning achievement in ICT where Fcount = 8,85 > Ftable = 4.00 at the level of significance α = 0.05. The conclusion of research is that application of the instructional media in the instructional process can improve the student’s learning achievement especially for PTE. Therefore, the implication is lecturers should be trained in order they can apply a more variative instructional process. So, it is the suggested that the lecturers should able use a variety of media for the success of the instructional process. Keywords : instructional media, multiple intelligences, interactive multimedia, module, spatial visual, verbal linguistic.